DESIGN OF THE SI-NANING MOBILE APP AS A DIGITAL INTERVENTION FOR ANEMIA AND STUNTING PREVENTION - Fidyah Aminin; Rahmadona, Rahmadona (Bajang Institute, 2025)
Stunting is a problem that needs special attention because of its high prevalence in Indonesia. Anemia in pregnant women is one of the factors that causes stunting. Based on preliminary studies, in Tanjungpinang City, there has been no digitization of Health Education about the prevention of anemia and stunting. This research aims to design and build an Android application called